Analisis Pengaruh Supervisi dan Budaya Organisasi Terhadap Kinerja Dosen Di Jurusan Farmasi Politeknik Kesehatan Kemenkes Palembang - Sidri Sidri; Sarmadi Sarmadi (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2012)
This research studies the influence of Supervition and Organizational Culture toward Lecturer Performance at at The Pharmacy Politeknik Kesehatan Kemenkes Palembang. This Research was done during 6 ( six) months included design, executing and report the result. The research of this case study aims to know the influence of Supervition and Organizational Culture with Lecturer Performance at The Pharmacy Politeknik Kesehatan Kemenkes Palembang either through parsial and also together. The population In this research are the Lecturer at The Pharmacy Politeknik Kesehatan Kemenkes Palembang, totally 32 people.